Association of Cerebral Palsy (CP) Child Behavior with Caregiver Stress Level - Asim Raza, Hafiz Muhammad; Jabeen, Hira; Ijaz, Atiq; Binash Afzal; Mumtaz, Sara; Hafiz Muhammad Bilal Hanif (International Health Review, 2026)
The disability which occurs frequently in children is known as cerebral palsy (CP). Its prevalence in Pakistan is much higher and about 2 to 3 out of every 1000 children are diagnosed with CP, which affectstheirfunctional status of life to a greater extent. The objective of the current study was to determine the association of CP child’s behavior with caregiver’s stress level. The current study was based on a cross sectional design and it comprised 159 caregivers of CP child. Among them 100 were males and 59 were females. The study was conducted within the time period from December 2016 to May 2017. A convenience sampling technique was used and subjects were selected from different hospitals and rehabilitation centers of Lahore, Pakistan on the basis of inclusion and exclusion criteria after taking informed consent. The two standardized “parental stress scale” and “strength difficulty questionnaire” helped to determine the level of stress and caregiver’ burden. The data was analyzed using SPSS v20. The frequency was calculated to obtain mean values of caregiver stress and behavior of CP child using PSS and SDQ. P value ≤ .05 was considered statistically significant. The Pearson correlation (r) between PSS and SDQ data was r₌ 0.63, which showed a strong positive linear correlation between the two variables, that is, CP child behavior & caregiver stress level. It indicated that both variables increased or decreased together. The behavior of CP child affects the quality of life of parents and caregivers. The study concluded that there is a strong relationship between the CP child’s behavior with the caregiver’s stress level.